Scavenging of reactive oxygen species by melatonin - Zang, Lun-Yi; Cosma, Greg; Gardner, Henry; Vallyathan, Val (Biochimica et biophysica acta, 1998)
The direct effects of the neurohormone melatonin on reactive oxygen species (ROS) were investigated. Melatonin was found to inhibit DMPO-O − 2 formation in a dose-dependent manner. At the level of 1.7±0.07 mM, melatonin caused 50% inhibition of EPR signal intensity of DMPO-O − 2during the reaction of xanthine and xanthine oxidase. The reaction rate constant of melatonin with O ⋅− 2 was found to be 1.25±0.07×10 3 M −1 s −1. However, melatonin (up to 1.2 mM) did not exhibit significant effect toward ⋅OH radical, produced by the Fenton reaction. In addition, we found no evidence for the formation of the melatonin indolyl cation radical that presumably precedes conversion of melatonin to its stable N 1-acetyl- N 2-5-methoxykynuramine (AMK) metabolite following sequential reactions of melatonin with O ⋅− 2 and ⋅OH. On the other hand, melatonin was capable of scavenging H 2O 2 in a dose-dependent manner with an IC 50=0.5±0.02 mM. The reaction rate constant of melatonin with H 2O 2 was found to be 2.52±0.19×10 5 M −1 s −1. Furthermore, melatonin was also found to inhibit 1O 2-dependent 2,2,6,6-tetramethylpiperidine oxide (TEMPO) radical formation during rose bengal photodynamic reaction. The results suggest that melatonin’s antioxidant properties, in part, may involve a direct effect on scavenging of ROS.